Surviving Academic Difficulties: Spirituality and Its Relationship to Resilience in Migrating Final-Year Students - Pinasthika, Terrymoza Demas; Ambarwati, Krismi Diah (Psikoborneo: Jurnal Ilmiah Psikologi, 2024)
One of the most challenging phases in college is the phase when working on a thesis. Moreover, as a student who is far from home, of course, you will have your own difficulties. To be able to face the difficulties in working on a thesis, of course, you must have a resilient nature in yourself, namely the ability to deal with pressure. Resilience is influenced by several factors, one of the factors that influences resilience is spirituality. This study aims to determine the relationship between spirituality and resilience in students who are working on their thesis. Participants in this study were 155 students from Satya Wacana Christian University. This study used an accidental sampling technique to obtain respondents. This study used the Resilience Quotient Test measuring instrument by Reivich and Shatte in 2002 with a reliability score of .916 and The Daily Spiritual Experience Scale (DSES) by Underwood in 2006 with a reliability score of .872. The normality test used in this study is the Kolmogorov-Smirnov test, the linearity test used is the Anova test, the hypothesis test that will be used in this study is by using the Pearson's product moment correlation technique, and there is also a partial test for each aspect of spirituality. The results of this study indicate a positive relationship between spirituality and resilience in migrant students who are working on their thesis, the Pearson Correlation value is 0.305 (Sig = 0.000). Therefore, the higher a person's level of spirituality, the higher their level of resilience.Salah satu fase paling menantang dalam perkuliahan adalah fase ketika sedang mengerjakan skripsi. Apalagi sebagai mahasiswa perantau yang jauh dari rumah tentu akan memiliki kesulitannya sendiri. Untuk dapat menghadapi kesulitan dalam pengerjaan skripsi tentunya harus memiliki sifat resilien dalam diri yaitu kemampuan untuk menghadapi tekanan. Resiliensi dipengaruhi oleh beberapa faktor  salah satu faktor yang mempengaruhi resiliensi adalah spiritualitas. Penelitian ini memiliki tujuan untuk mengetahui hubungan antara spiritualitas dan resiliensi pada mahasiswa perantau yang sedang mengerjakan skripsi. Partisipan dalam penelitian ini adalah 155 mahasiswa perantau Universitas Kristen Satya Wacana. Penelitian ini menggunakan teknik accidental sampling untuk mendapatkan responden. Penelitian ini menggunakan alat ukur Resilience Quotient Test milik Reivich dan Shatte tahun 2002 dengan skor reliabilitas .916 dan The Daily Spiritual Experience Scale (DSES) milik Underwood tahun 2006 dengan skor reliabilitas .872 .  Uji normalitas yang digunakan dalam penelitian ini adalah uji Kolmogorov-Smirnov, Uji linearitas yang digunakan adalah uji Anova, uji hipotesis yang akan digunakan pada penelitian ini adalah dengan menggunakan teknik korelasi Pearson’s product moment, dan ada juga uji parsial untuk tiap aspek Spiritualitas. Hasil dari penelitian ini menunjukan adanya hubungan yang positif antara spiritualitas dengan resiliensi pada mahasiswa perantau yang sedang mengerjakan skripsi nilai Pearson Correlation 0.305 (Sig=0.000). Oleh karena itu semakin tinggi tingkat spiritualitas seseorang maka semakin tinggi pula tingkat resiliensinya.